«ИЗ ГАЗЕТ»: НА ЧАЛОПЕРВОЙ МИРОВОЙ ВОЙНЫ В РУССКИХ ПОЭТИЧЕСКИХ ТЕКСТАХ - Минутина-Лобанова, Юлия (Przegląd Rusycystyczny, 2016)
“THROUGH NEWSPAPERS ”: THE BEGINNING OF THE WORLD WAR I IN RUSSIAN POETRY S u m m a r y This paper concentrates on the Russian poetry in newspapers in summer 1914 about the beginning of the First World War. The analysis revealed the main poetics and subject characteristics of these poems, such as proper nouns abundance, active usage of the historicisms and archaisms, the combination of enthusiastic attitude to war and its perception as irrelevant events etc. Thereby we can evaluate the immediate perception of the beginning of the war by contemporaries and get an overview of poetical and informational context in Russia in July–August 1914.